KEWENANGAN BRIMOB DALAM PENGENDALIAN UNJUK RASA BERDASARKAN PERATURAN KAPOLRI NOMOR 16 TAHUN 2006 - I Nyoman Suandika; I Nyoman Suryana (Universitas Mahendradatta, 2025)
As an elite unit trained to deal with riots and public disturbances, Brimoboften faces significant challenges in managing mass demonstrations that sometimesescalate into riots. Therefore, it is crucial to examine the legal protections for Brimobmembers in carrying out crowd control duties, ensuring that these duties remain inaccordance with applicable law and respect human rights.